Implementing ludic strategies for the development of english oral skills - Jiménez Rivera, Graciela Desirée; Atiencia Pogo, Shirley Cristina (Machala: Universidad Técnica de Machala, 2024)
The main objective of the present research was to implement a classroom system using playful strategies to improve high school students' oral communication skills in English language learning. The specific objective included analyzing the methods and activities currently employed in English language teaching, assessing students' initial levels of oral proficiency, designing a classroom system that integrates playful activities, and evaluating the results after implementation. The study employed an empirical-analytical quantitative approach to examine the factors contributing to students' challenges in oral communication. Data were collected using non- participant observation, diagnostic assessments, rubrics, and structured questionnaires. Post-test results demonstrated significant improvements across all indicators, fluency, pronunciation, grammar, and content, compared to the pre-test. It confirms that the application of play strategies significantly improved the students' oral communication skills. The findings show that playful activities create a fun and interactive learning environment. They boost participation, lower anxiety, and help students use the language naturally and effectively. That's why teachers should regularly use these strategies in English classes at both primary and secondary levels.
El objetivo principal de la presente investigación era implantar un sistema de aula que utilizara estrategias lúdicas para mejorar las destrezas comunicativas orales de los estudiantes de secundaria en el aprendizaje de la lengua inglesa. El objetivo específico incluía analizar los métodos y actividades empleados actualmente en la enseñanza del inglés, evaluar los niveles iniciales de competencia oral de los estudiantes, diseñar un sistema de aula que integre actividades lúdicas y evaluar los resultados tras la implementación. El estudio empleó un enfoque cuantitativo empírico-analítico para examinar los factores que contribuyen a los retos de los estudiantes en la comunicación oral. Los datos se recogieron mediante observación no participante, evaluaciones de diagnóstico, rúbricas y cuestionarios estructurados. Los resultados posteriores a la prueba demostraron mejoras significativas en todos los indicadores, fluidez, pronunciación, gramática y contenido, en comparación con la prueba previa. Se confirma que la aplicación de estrategias lúdicas mejoró significativamente las habilidades de comunicación oral de los alumnos. Los resultados muestran que las actividades lúdicas crean un entorno de aprendizaje divertido e interactivo. Aumentan la participación, disminuyen la ansiedad y ayudan a los alumnos a utilizar la lengua con naturalidad y eficacia. Por eso los profesores deberían utilizar regularmente estas estrategias en las clases de inglés, tanto en primaria como en secundaria
Keywords: SPEAKING; SKILL; TEACHING; ENGLISH